A Feasibility study of a training generating mechanism of the National Engineering Center - Cusi, Ma. Belinda; Palomares, Samuel; Plata, Melynda; Sanchez, Joselito; Yu, Jeanie (College of Engineering, 1982)
The National Engineering Center was created as a distinct unit of the University of the Philippines by Presidential Decree No. 1295 on January 27, 1978. Its objectives are: (1) to provide a pool of technical experts to which public and private entities may turn for assistance in the solution of engineering problems. (2) to develop technologies that utilize local resources which are adapted to the needs of a developing country. National Engineering Center was established as a response to the country's continuing efforts at national development and well being which require progressive and adequate technological utilization and diffusion. It is recognized that more rapid national development demands a steady and expanding supply of technical manpower and expertise in the various fields of technology and engineering and on updating existing technical manpower. In addition, continuing interaction between government, industry and the university are mutually beneficial and in the interest of national government. In this regard, this study was undertaken to determine the feasibility of a Training Program generating office of the NEC specifically the Project Development Office. The Market Analysis of this study aims to survey the different technological needs of the different foundations, the private industries and the government sector. It will also try to identify the target clientele of the Training Program that will be generated and the profile of such clients. It is hoped that with this information, marketing strategies could be designed to tap this huge training market potential. The Technical Analysis will delve on the determination of the capability of National Engineering Center in satisfying the determined technological needs. The systems and procedures in the conduct of the various training programs will be developed. Determination of the cost components of a training program, project costing, five-year projections, and financial viability of the training programs will be tackled in the Financial Analysis.